Analysis of the Telecommunication Companies’ Capital and its Structure Optimization - Sergeevna, Filonova Elena (Journal of Reviews on Global Economics, 2018)
The search for optimal capital structure of a company is an important task of the strategic financial management. The paper given is a natural continuation of a series of author’s publications on the study of problems connected with building an optimal capital structure of a company (Ageev and Filonova, 2017), (Filonova ES, 2017). The practical part of the research conducted deals with the leaders of the Russian telecommunication market «Rostelecom», «MTS», «MegaFon», «Vimpel-Communications» and there were some attempts to build an optimal capital structure in the strategic group of competitors, based on the materials of accounting (financial) reports of these companies as at 2014 and 2015. The present paper contains the analysis of the actual capital structure of the companies mentioned above based on studying their balance sheets, made as at the end of 2016, and gives the results of the search for optimal capital structure based on the data in the new accounting period.